The Development of Education in Jordan in 2023: Challenges, Innovations, and Future Prospects - Mohammad Ahmad Bani Amer (International Journal of Education and Digital Learning (IJEDL), 2023)
The education system in Jordan has undergone significant transformations over the past decade. This paper explores the development of education in Jordan in 2023, focusing on the advancements, challenges, and the role of technological innovations in shaping the educational landscape. Key factors such as government policies, economic considerations, and the role of international organizations are discussed. In particular, the study examines the integration of digital learning platforms, efforts to improve the quality of teaching, and the expansion of higher education institutions. The paper also addresses the impact of the COVID-19 pandemic on education in Jordan and how the system adapted through hybrid learning models and digital tools. Furthermore, this research highlights the current state of public and private education in Jordan, identifying disparities and opportunities for growth. Recommendations for further development are provided, including the need for more investment in teacher training and the establishment of more inclusive education policies. By focusing on the year 2023, the study provides an up-to-date snapshot of the ongoing challenges and reforms, offering insights into the future trajectory of education in Jordan.